Serum creatinine/cystatin C ratio as a case-finding tool for low handgrip strength in Chinese middle-aged and older adults - Tan, Lingling (Sci Rep, 2020)
Measuring handgrip strength is the initial step to diagnose sarcopenia. To investigate whether the serum creatinine (Cr)/cystatin C (CysC) ratio could serve as a case-finding tool for low handgrip strength, we conducted a diagnostic accuracy study. Adults (aged ≥ 40 years) with normal renal function were recruited. Trained nurses collected blood samples and conducted the anthropometric measurements and handgrip strength test. The serum concentrations of Cr, CysC, and other biomarkers were measured. We recruited 1098 men and 1241 women. The Cr/CysC ratio was significantly associated with AWGS-defined low handgrip strength among men and women. The areas under the receiver operating characteristic curves were 0.79 among men and 0.78 among women for using the Cr/CysC ratio to identify AWGS-defined low handgrip strength. We set the Cr/CysC ratio cut-off values at < 8.9 among men and < 8.0 among women. The corresponding sensitivity values were 64.9% among men and 63.1% among women, while the specificity values were 83.7% among men and 77.5% among women. In conclusion, the Cr/CysC ratio is positively and linearly associated with handgrip strength and may be helpful for screening low handgrip strength in Chinese middle-aged and older adults dwelling in communities.